Z dziejów wykładników kwantyfikacji. Rzeczowniki odliczebnikowe z sufiksami -ka i -ek - Janowska, Aleksandra (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article is devoted to the problems associated with historical word formation. It explores the evolution of denumeral nouns (formed from collective and cardinal numerals) by means of the suffixes -ek and -ka (cf. e.g. czwórka, dziewiątka, dziesiątek). Along with numerals and other classes of nouns they enter the process of expressing various kinds of quantification. The changes within these formations and their bases are strictly interrelated. The history of the Polish language reveals a slow expansion of the word-formative model in question, which coincides in a natural manner with the crystallisation of the class of numerals and the transformations of their syntactic and inflectional properties. It is these processes that paved the way for the formations with -ka and -ek. These nouns are polysemic in nature, they may indicate number, collectivity or the attributes of objects. The article points out the evolution of the two former senses – the most important ones, which are, contrary to what may appear, changeable in terms of their historical development, cf, e.g. the early dziewiątek złotych, sześć dziesiątków lat. It is worth pointing out that in some contexts the derivatives in question may perform the same function as that of a numeral – both a cardinal and a collective numeral. The research is largely based on the material drawn from dictionaries and linguistic corpora.